Information and Communication Technologies and Broad-Based Development : A Partial Review of the Evidence - Grace, Jeremy; Kenny, Charles; Zhen-Wei Qiang, Christine; Liu, Jia; Reynolds, Taylor (Washington, DC: World Bank, 2013)
Information and communication technologies (ICTs) are increasingly seen as integral to the development process. This paper reviews some of the evidence for the link between telecommunications and the Internet and economic growth, the likely impact of the new ICTs on income inequality and anecdotal evidence regarding the role of the Internet in improving government services and governance. It looks at methods to maximize access to the new ICTs, and improve their development impact both in promoting income generation and the provision of quality services.